Laser operated borate polymer nanocomposites - Ali Hussain, Reshak, Prof. Dr.; Gandham, Lakshminarayana; Burak, Ya V.; Adamiv, Volodymyr T. (Elsevier B.V., 2011)
Link to publisher's homepage at http://www.elsevier.com/